Análise econômica do direito sobre aspectos da reforma previdenciária Brasileira de 2019 na perspectiva dos segurados do regime geral da previdência social - Elias, Ronaldo (2022)
The current Brazilian social security system, implemented since the Federal Constitution of 1988, underwent a broad reform with the entry into force of Constitutional Amendment No. 103/2019, which had as its fundamental argument the need to overcome the deficit caused in public accounts, which it would be a substitute for maintaining the system itself and bypassing the fiscal knot that suffocates the primary debt of public accounts, making investment in other areas impossible. In this step, taking into account that this reform provided the mitigation of social security rights, in the sense of reducing the value of benefits and increasing the contribution necessary to obtain them, from two antagonistic perspectives, one economic and the other focused on demands for security. social, this work promotes, through the methodological aspects of the Economic Analysis of Law - AED, complemented by the designs of the constitutional jusfundamentality of social rights, an analysis, with empirical applications, of essential points of pension reform from the perspective of those insured under the General Social Security Regime - RGPS, especially with regard to the rules that increased and increased the requirements necessary to obtain social security benefits and reduced the value of the monthly remuneration paid, seeking to highlight the extent to which the standards of said reform are really economically effective and encouraging to RGPS policyholders, in order to obtain the maximization of wealth and the efficiency of economic and social well-being, and how the maximizing and efficient allocation of public resources permeates the responsibility and observance of constitutional designs on the part of the public administrator when resulting from the sacrifices and social concessions made in order to save money to guarantee a surplus in public accounts. The hypothetical-deductive method, bibliographic research on books, scientific articles and electronic media, as well as statistical analyzes obtained through data collected by public bodies, were used as research resources. Given this panorama, it was concluded that, although necessary, the reform caused externalities that need to be overcome and that the economic sacrifices now made by RGPS policyholders need to be compensated by the efficient allocation of public budgetary resources saved.